2022
DOI: 10.1055/a-1929-9500
|View full text |Cite
|
Sign up to set email alerts
|

Do First-Trimester Subchorionic Hematomas Affect Pregnancy Outcomes?

Abstract: Objective The aim of this study is to investigate the relationship between first trimester subchorionic hematomas and pregnancy outcomes in women with singleton pregnancies. Material and methods Between January 2018 and January 2019, patients who had a single pregnancy between the 6th and 14th weeks of their pregnancy and were hospitalized with the diagnosis of abortus imminens in the early pregnancy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…A study indicated that the size of the hematoma estimated as a fraction of gestational sac size significantly correlated with first-trimester pregnancy loss [12]. In our study, similar to the conclusion of studies in 2019 [10] and in 2022 [27], the estimated size of SCH was not associated with miscarriage. The presence or absence of a hematoma may be one of the indicators that the placenta was functioning properly, independent of its number and size.…”
Section: Discussionsupporting
confidence: 89%
“…A study indicated that the size of the hematoma estimated as a fraction of gestational sac size significantly correlated with first-trimester pregnancy loss [12]. In our study, similar to the conclusion of studies in 2019 [10] and in 2022 [27], the estimated size of SCH was not associated with miscarriage. The presence or absence of a hematoma may be one of the indicators that the placenta was functioning properly, independent of its number and size.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, some studies have reported that the presence of SCH increases the risk of adverse pregnancy outcomes such as abortion, premature delivery and premature rupture of membranes, for example, Li Y and Alijotas J et al found that compared with normal pregnant women, the positive rate of autoantibodies such as anti-nuclear antibodies and anti-cardiolipin in SCH patients increased. [4,5] Several studies have reported the effect of SCH on pregnancy outcomes, such as SCH was associated with an increased risk of spontaneous abortion, preterm birth and premature rupture of membranes (PROM). [6,7] The exact etiology of SCH is still unclear.…”
Section: Introductionmentioning
confidence: 99%